2020
DOI: 10.1002/bmc.4741
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic therapeutic effects of Duzhong Jiangya Tablets and amlodipine besylate combination in spontaneously hypertensive rats using 1H‐NMR‐ and MS‐based metabolomics

Abstract: Duzhong Jiangya Tablet (DJT) composed of Eucommia ulmoides Oliv. and several other traditional Chinese medicines is a Chinese herbal compound, which is clinically used to treat hypertension. The aim of this study was to evaluate the antihypertensive effect of DJT and amlodipine besylate (AB) on the synergistic treatment of spontaneously hypertensive rats (SHRs), and to explore its antihypertensive mechanism. The synergistic therapeutic effect of DJT in combination with AB on SHR was studied using two metabolom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…In this study, EU improved the blood pressure and ameliorated the kidney injury in hypertensive mice subjected to an HSD and L-NAME treatment, which is consistent with previous findings in Dahl salt-sensitive rats ( Ishimitsu et al, 2021 ) and SHRs ( Li et al, 2012 , 2020 ). For example, Eucommia lignans ameliorated renal dysfunction, with decreased aldose reductase and collagen type III, in SHRs and inhibited the proliferation of renal mesangial cells induced by angiotensin II ( Li et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, EU improved the blood pressure and ameliorated the kidney injury in hypertensive mice subjected to an HSD and L-NAME treatment, which is consistent with previous findings in Dahl salt-sensitive rats ( Ishimitsu et al, 2021 ) and SHRs ( Li et al, 2012 , 2020 ). For example, Eucommia lignans ameliorated renal dysfunction, with decreased aldose reductase and collagen type III, in SHRs and inhibited the proliferation of renal mesangial cells induced by angiotensin II ( Li et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…(EU) is a small tree and EU extract is widely used in East Asia ( Wu et al, 2018 ; Ding et al, 2020 ), due to its wide range of pharmacological effects such as anti-hypertension, anti-inflammatory, anti-hyperlipidemia, anti-diabetes, anti-oxidant, and anti-tumor effects ( Shao et al, 2015 ; Zhang et al, 2022 ). In particular, the EU bark has been used for thousands of years in traditional Chinese medicine to improve hypertension ( Li et al, 2020 ). The chemical constituents of the EU bark extract include lignans, iridoids, flavonoids, phenols, steroids, fatty acids, volatile oils, antifungal proteins, and gutta-percha ( He et al, 2018 ; Wang C. Y. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that angiotensin-converting enzyme (ACE) inhibitory peptides could inhibit ACE and control blood pressure elevation in spontaneously hypertensive rats (SHRs), which were used for the study of hypertension disease owing to similar pathophysiological processes with essential hypertension. [3][4][5] Recently, the metabolomics approach has been employed to investigate the regulatory effect of drugs and natural products on in vivo metabolic profile changes in SHRs, [6][7][8][9][10][11][12] providing a new way to reveal the mechanism of natural bioactive peptides. There are very limited studies that have reported the mechanism underlying the antihypertensive effects of peptides via metabolomics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the combination of E. ulmoides and Tribulus terrestris showed anti-hypertensive effects in spontaneously hypertensive rats, possibly by regulating intestinal microbiota and beneficial metabolites [122]. Some marketed formulas containing E. ulmoides, such as Duzhong Jiangya tablets and Quan-E. ulmoides capsules, have been used clinically for the treatment of hypertension [123,124].…”
Section: Hypertensionmentioning
confidence: 99%